SlCNGC1 and SlCNGC14 Suppress Xanthomonas oryzae pv. oryzicola-Induced Hypersensitive Response and Non-host Resistance in Tomato - Zhang, Xuan-Rui; Xu, You-Ping; Cai, Xin-Zhong (Frontiers in Plant Science, 2018)
Mechanisms underlying plant nonhost resistance to Xanthomonas oryzae pv. oryzicola (Xoc), the pathogen causing rice leaf streak disease, are largely unknown. Cyclic nucleotide-gated ion channels (CNGCs) are calcium-permeable channels that are involved in various biological processes including plant resistance. In this study, functions of two tomato CNGC genes SlCNGC1 and SlCNGC14 in nonhost resistance to Xoc were analyzed. Silencing of SlCNGC1 and SlCNGC14 in tomato significantly enhanced Xoc-induced hypersensitive response (HR) and nonhost resistance, demonstrating that both SlCNGC1 and SlCNGC14 negatively regulate nonhost resistance related HR and nonhost resistance to Xoc in tomato. Silencing of SlCNGC1 and SlCNGC14 strikingly increased Xoc-induced callose deposition and strongly promoted both Xoc-induced and flg22-elicited H2O2, indicating that these two SlCNGCs repress callose deposition and ROS accumulation to attenuate nonhost resistance and PAMP-triggered immunity (PTI). Importantly, silencing of SlCNGC1 and SlCNGC14 apparently compromised cytosolic Ca2+ accumulation, implying that SlCNGC1 and SlCNGC14 function as Ca2+ channels and negatively regulate nonhost resistance and PTI-related responses through modulating cytosolic Ca2+ accumulation. SlCNGC14 seemed to play a stronger regulatory role in the nonhost resistance and PTI compared to SlCNGC1. Our results reveal the contribution of CNGCs and probably also Ca2+ signaling pathway to nonhost resistance and PTI.